Предмет: Алгебра,
автор: Знанчик111
Доказать тождество. СРОЧНО
Приложения:
Ответы
Автор ответа:
0
Преобразуем левую часть
(sin^4a-sin^6a)+(cos^4a-cos^6a)=sin^4a(1-sin^2a)+cos^4a(1-cos^2a=
=sin^4a*cos^2a+cos^4a*sin^2a=sin^2a*cos^2a*(sin^2a+cos^2a)=
=sin^2a*cos^2a *1=sin^2a*cos^2a
sin^2a*cos^2a=sin^2a*cos^2a
(sin^4a-sin^6a)+(cos^4a-cos^6a)=sin^4a(1-sin^2a)+cos^4a(1-cos^2a=
=sin^4a*cos^2a+cos^4a*sin^2a=sin^2a*cos^2a*(sin^2a+cos^2a)=
=sin^2a*cos^2a *1=sin^2a*cos^2a
sin^2a*cos^2a=sin^2a*cos^2a
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Литература,
автор: volkovaalen
Предмет: География,
автор: leras200801
Предмет: Математика,
автор: аида62